Combining Effect of Different Rates of Sorghum bicolor (L.) Moench Residues and Reduced Rates of Trifluralin on Weeds in Mung Bean Field - Z. Al-Obaidi, Laith; S. Alsaadawi, Ibrahim (Iraqi Journal of Science, 2023)
Field and laboratory experiments were performed to evaluate the allelopathicpotential of sorghum residues alone or in combination with reduced rate of trifluralinherbicide on weeds in mung bean field. The field experiment was conducted during2014 season at the Research Farm of Biology Department, College of Science,Baghdad University by using randomized complete Block design (RCBD) to test theeffect of sorghum residues at rates of 5 and 10 t ha-1 alone or in combination withreduced doses of trifluralin (30 and 60% of recommended dose) on weeds and mungbean crop. Weedy check and label rate of trifluralin (2.4 Lha-1) were also includedfor comparison. Each treatment was replicated four times. Total phenolics in fieldsoil amended with sorghum residues at 10 t ha-1 was determined in at 0, 14, 28 and42 days of sorghum residues decomposition. Also bioassay experiment wasconducted to test the allelopathic effect of sorghum residues at 10 t ha-1incorporated into the field soil on seedling emergence and growth of Portulacaoleracea weed during the above mentioned decomposition periods. Results showedthat incorporation of sorghum residues at 5 t ha-1 reduced weed density by16.9 and18.8% of control after 30 and 60 days from sowing, respectively. The reduction wasincreased when sorghum residues were incorporated at 10 t ha-1 and reached to 30and 30.5% of the control after 30and 60 days from sowing, respectively. However,the suppression of weed population and dry weight biomass was further improvedwhen the plots were treated with 30 and 60% of label rate of trifluralin and sorghumresidues at 5and 10 t ha-1. The highest suppression of weed population and drybiomass was achieved by application of reduced rate of trifluralin (60%) to plotsamended with sorghums residues at 10 t ha-1. Integration of reduced herbicide andsorghum residues at 5and 10 t ha-1 resulted in more weed suppression than soleapplication of the respected sorghum residues. The results also revealed that weedsuppression was directly translated into yield of mung bean. Application oftrifluralin herbicide at 60% of label rate in plots amended with sorghum residues at10 t ha-1 recorded the highest biological and grain yield, number of pods per plantsand weight of 100 seeds. Chemical analysis indicated that total phenolics started toincrease at14 and 28 days of decomposition and decline thereafter until vanished 6weeks of decomposition. Biological activity test of field soil revealed thatsuppression of Portulaca oleracea weed was highly correlated with total phenolics(R2 = 0.95for seedling emergence and 0.87 for dry biomass) of soil suggesting thathigh weed suppression was mainly due to high activity of phenolics.